SKAP2 regulates Arp2/3 complex for actin-mediated asymmetric cytokinesis by interacting with WAVE2 in mouse oocytes. Issue 23 (2nd December 2017) - He, Shu-Wen; Xu, Bai-Hui; Liu, Yu; Wang, Ya-Long; Chen, Ming-Huang; Xu, Lin; Liao, Bao-Qiong; Lui, Rui; Li, Fei-Ping; Lin, Yan-Hong; Fu, Xian-Pei; Fu, Bin-Bin; et al.
ABSTRACT: SKAP2 (Src kinase-associated phosphoprotein 2), a substrate of Src family kinases, has been suggested to be involved in actin-mediated cellular processes. However, little is known about its role in mouse oocyte maturation. In this study, we thus investigated the expression, localization, and functions of SKAP2 during mouse oocyte asymmetric division. SKAP2 protein expression was detected at all developmental stages in mouse oocytes. Immunofluorescent staining showed that SKAP2 was mainly distributed at the cortex of the oocytes during maturation. Treatment with cytochalasin B in oocytes confirmed that SKAP2 was co-localized with actin. Depletion of SKAP2 by injection with specific short interfering RNA caused failure of spindle migration, polar body extrusion, and cytokinesis defects. Meanwhile, the staining of actin filaments at the oocyte membrane and in the cytoplasm was significantly reduced after these treatments. SKAP2 depletion also disrupted actin cap and cortical granule-free domain formation, and arrested a large proportion of oocytes at the telophase stage. Moreover, Arp2/3 complex and WAVE2 expression was decreased after the depletion of SKAP2 activity. Our results indicate that SKAP2 regulates the Arp2/3 complex and is essential for actin-mediated asymmetric cytokinesis by interacting with WAVE2 in mouse oocytes.